Question
upstudy study bank question image url

Part 2: Algebraic Logarithm (5 points) Given the equation \( \log (2 x-3)+\log 8=\log (9 x+11) \), show all steps used to solve for \( x \).

Ask by Gibbs Mckenzie. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x = 5 \)

Solution

Step 1: Determine the Domain • For log(2x - 3) to be defined, its argument must be positive:   2x - 3 > 0 ⟹ x > 3/2. • For log(9x + 11) to be defined, we require:   9x + 11 > 0 ⟹ x > -11/9. Thus, the overall domain is x > 3/2 (since 3/2 > -11/9). Step 2: Combine the Logarithms Use the property that log A + log B = log (A·B):   log(2x - 3) + log(8) = log[8(2x - 3)] So the equation becomes:   log[8(2x - 3)] = log(9x + 11). Step 3: Equate the Arguments Since the logarithms are equal and within the domain, their arguments must be equal:   8(2x - 3) = 9x + 11. Step 4: Solve the Equation • Expand the left side:   16x - 24 = 9x + 11 • Subtract 9x from both sides:   16x - 9x - 24 = 11   7x - 24 = 11 • Add 24 to both sides:   7x = 35 • Divide both sides by 7:   x = 5 Step 5: Verify the Solution Against the Domain Check that x = 5 satisfies the domain x > 3/2. Since 5 > 1.5, the solution is valid. Final Answer: x = 5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( \log (2x - 3) + \log 8 = \log (9x + 11) \), we can start by using the property of logarithms that states \( \log a + \log b = \log (ab) \). 1. Combine the logarithms on the left side: \[ \log (2x - 3) + \log 8 = \log (8(2x - 3)). \] So the equation becomes: \[ \log (8(2x - 3)) = \log (9x + 11). \] 2. Since the logarithms are equal, we can set the arguments equal to each other: \[ 8(2x - 3) = 9x + 11. \] 3. Distribute the 8 on the left side: \[ 16x - 24 = 9x + 11. \] 4. Rearranging the equation, we move \( 9x \) to the left side and \( -24 \) to the right side: \[ 16x - 9x = 11 + 24. \] 5. This simplifies to: \[ 7x = 35. \] 6. Divide both sides by 7 to solve for \( x \): \[ x = 5. \] 7. Lastly, we need to check if this value satisfies the original equation by substituting \( x = 5 \) back in: - Calculate \( 2(5) - 3 = 10 - 3 = 7 \). - Calculate \( 9(5) + 11 = 45 + 11 = 56 \). - Check the logarithmic terms: \[ \log(7) + \log(8) = \log(56) \] which is true since \( \log(7 \times 8) = \log(56) \). Therefore, the solution to the equation is \( x = 5 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy